Corporate Governance Index, Corporate Ownership Structure and Audit Committee on Debt Costs - Siti Nur Azizah; Yulia Nurcahyani (Faculty of Economics and Business Universitas Muhammadiyah Riau, 2020)
This study aims to analyze corporate governance index and ownership structure and audit committee on the cost of debt. The study based on agency theory by Jensen and Meckling in 1976. This study use secondary data derived from financial statements of companies participating in the Corporate Governance Perception Index (CGPI) for 2014-2018 which are listed on the Indonesia Stock Exchange. The method of data collection in this study used purposive sampling. The data was analyzed by multiple linear regression analysis. The results of this study indicate that corporate governance index and institutional ownership negatively effect on the cost of debt. In contrast, audit committee and managerial ownership has no impact on the cost of debt. The findings in this study can be beneficial for investors in assessing the governance of a company in managing its debt. Investors can consider for an investment decision both long term and short term.